Parental Involvement and Its Contribution to Students’ Academic Achievement - Bhandari, Ram Bahadur (International Research Journal of MMC (IRJMMC), 2025)
The primary objective of this study is to explore the role of parental support in enhancing students' overall academic achievement. Specifically, the study investigates parental support as an independent variable and student achievement as the dependent variable. The research adopts a quantitative approach, employing a questionnaire survey as the primary data collection method. The collected data have been analyzed using descriptive statistics to interpret the relationship between parental involvement and student performance. A total of 386 students were selected for the study using a stratified sampling method to ensure balanced representation from diverse groups. These students were from the secondary level of 20 different schools located in Makawanpur District, Bagmati Province, Nepal. The research utilized a cross-sectional survey design to collect data at a single point in time, capturing students’ perceptions and experiences regarding parental involvement in their education. The findings of the study reveal that students whose parents, especially mothers and fathers, remain at home and actively support their learning and personal care tend to perform better academically. Regular assistance in completing homework, engagement in academic discussions, and emotional encouragement from parents are significant contributors to students’ improved academic outcomes. The study concludes that consistent parental support, both emotional and academic, plays a crucial role in boosting students’ achievement levels. These results highlight the importance of fostering strong home-school connections and encouraging parents to be actively involved in their children’s education to ensure better academic performance and holistic development.